Transported : 50 vehicles that changed the world - Ralphs, Matt (Nosy Crow Inc, 2023)
From ancient chariots and Viking longships to racing cars, rockets, and solar-powered airplanes, our world has been changed by the pioneering development of many incredible vehicles. Take a journey through time to discover how these 50 groundbreaking inventions changed the world and how they might even shape our future . . .